INNOVATIVE APPROACHES IN TEACHING AND LEARNING OF WORLD LITERATURE IN HIGHER SCHOOL - Hrytsak, Natalia (Educological discourse, 2018)
The article deals with theoretical substantiating of the concepts “innovative education” and “innovative technologies”. The state of scientific researches of the problem of the introduction of innovative technologies in the educational process of students-philologists in higher school is explored. Three aspects of the notion “innovation” are examined in the article. The principle components of innovative education are analyzed. Innovative education predicts a new inquiry-based approach in teaching the traditional learning courses at the faculty of philology of higher educational establishments. The role and importance of information technologies are exposed; the expedience of the introduction of new information technologies in the educational process of higher educational establishments is advanced arguments. It is demonstrated that the tendencies of the development of higher education in Ukraine require the search and realization of different forms, methods, principals of education which facilitate the progress high results in educational process. The concept innovative pedagogical activity is ascertained. Innovative education is the realization of the novelty in contents, methods, techniques and forms of education. Innovative education is the opposition to the traditional forms of education as provides changing of educational priority. One of the principle aspects of the problem of the effective introduction of Innovative education is removal accent of lecturer’s functions. Innovative pedagogue’s activity needs special knowledge, skills and mastering logical thinking, creativity and finding the ways of solving the problem. Innovative pedagogical activity is the activity in consequence of which the complex of developed (different levels of complexity), novelty or reinterpretation, and accordingly creative realization of the heritage of other scholars and pedagogues is developed. The author partly propounds the most effective methods and forms of educational work of students-philologists at the classes of world literature of the institutions of higher education. It is defined that the application of innovative technologies concentrates the student audience’s attention, stimulates the retention of educational material, forms the information culture of students-philologists, and improves creative components of the traditional forms of education.